Rethinking the Study of Electoral Politics in the Developing World: Reflections on the Indian Case. Issue 1 (22nd March 2022) - Auerbach, Adam Michael; Bussell, Jennifer; Chauchard, Simon; Jensenius, Francesca R.; Nellis, Gareth; Schneider, Mark; Sircar, Neelanjan; Suryanarayan, Pavithra; Thachil, Tariq; Vaishnav, Milan; Verma, Rahul; Ziegfeld, Adam
Abstract : In the study of electoral politics and political behavior in the developing world, India is often considered to be an exemplar of the centrality of contingency in distributive politics, the role of ethnicity in shaping political behavior, and the organizational weakness of political parties. Whereas these axioms have some empirical basis, the massive changes in political practices, the vast variation in political patterns, and the burgeoning literature on subnational dynamics in India mean that such generalizations are not tenable. In this article, we consider research on India that compels us to rethink the contention that India neatly fits the prevailing wisdom in the comparative politics literature. Our objective is to elucidate how the many nuanced insights about Indian politics can improve our understanding of electoral behavior both across and within other countries, allowing us to question core assumptions in theories of comparative politics.